2004
DOI: 10.2516/ogst:2004011
|View full text |Cite
|
Sign up to set email alerts
|

Elements for an Integrated Geostatistical Modeling of Heterogeneous Reservoirs

Abstract: Résumé -Éléments pour une modélisation géostatistique intégrée de réservoirs hétérogènes -L'approche géostatistique pour la modélisation des réservoirs hétérogènes permet, d'une part, d'intégrer l'ensemble des données de natures diverses et d'échelles différentes, et d'autre part, d'évaluer les incertitudes par génération de multiples scénarios possibles. La conception d'un modèle géostatistique de réservoir doit d'abord dépendre de l'environnement de dépôt géologique, ce qui permet de représenter les hétérogé… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…However, one disadvantage is that their methods of populating the facies distributions between control wells are not necessarily constrained by geological reasoning. A second disadvantage is that the simulated geometries of individual bodies are not necessarily continuous (Journel & Deutsch, 1993; Hu & Le Ravalec‐Dupin, 2004). The tests carried out in the present study, have shown that at the inter‐well scale (×10 to ×100 m), TGSim (Models A and B) and SISim (Model C) provide a reasonable approximation of the lithofacies proportion, distribution and heterogeneity (Table 2; Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, one disadvantage is that their methods of populating the facies distributions between control wells are not necessarily constrained by geological reasoning. A second disadvantage is that the simulated geometries of individual bodies are not necessarily continuous (Journel & Deutsch, 1993; Hu & Le Ravalec‐Dupin, 2004). The tests carried out in the present study, have shown that at the inter‐well scale (×10 to ×100 m), TGSim (Models A and B) and SISim (Model C) provide a reasonable approximation of the lithofacies proportion, distribution and heterogeneity (Table 2; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Three algorithms, TGSim, SISim and IK, were tested because they are the most commonly used for facies modelling in PETREL™ (Trademark of Schlumberger) (Journel et al. , 1998; Hu & Le Ravalec‐Dupin, 2004; Falivene et al. , 2006a).…”
Section: Introductionmentioning
confidence: 99%
“…A GDM-driven optimization is actually a sequence of optimizations. The interested reader can refer to Hu (2000), Hu et al (2001a) or Hu and Le Ravalec-Dupin (2004a) to get more details about the GDM.…”
Section: Global Gradual Deformationmentioning
confidence: 99%
“…In step (a) (Figure 2a), ϕ s is computed over the domain using equation (3) and ϕ R is generated according to the fast Fourier transform moving average approach and structural deformation technique (Hu, 2000;Hu & Le Ravalec, 2004;Le Ravalec et al, 2000). For this, we select a mean, a variance, the integral scales which measure the correlation distance in space in the x-y axis (l x and l y ), a Gaussian covariance model, and a uniform white noise or uncorrelated uniform random field.…”
Section: Subglacial Channel Network Generatormentioning
confidence: 99%